EVALUASI KAPABILITAS AUDIT INTERNAL PADA PERWAKILAN BPKP PROVINSI KALIMANTAN TIMUR - imam Nazarudin Latief (RJABM (Research Journal of Accounting and Business Management), 2018)
This study aims to determine (1) To know the understanding of the enhancement of APIP capability by using Internal Audit Capability Model (IA-CM) (2) To know the internal audit capability level at the BPKP Representative of East Kalimantan Province and the efforts to be taken to improve and maintain it. This research was conducted at BPKP Representative of East Kalimantan Province. Period assessed by the author's internal audit capability is the period of 2016.This research is conducted by field research and literature research by reading the literature related to the problem under study. The data used to evaluate internal audit capability at BPKP Representative of East Kalimantan Province is data of internal audit capability condition of BPKP Representative of East Kalimantan Province. The analytical tool used in this research is Head of BPKP Regulation No. 16 of 2015 on Technical Guidelines for Capacity Improvement of Government Internal Supervisory Apparatus.The result of this research is internal audit capability of BPKP Representative of East Kalimantan Province on elements of Role and Service, Professional Practice, Accountability and Performance Management, Organizational Relations and Culture, The Governance Structure is at level 3 (integrated), while the element of Human Resource Management is at level 2 (infrastructure). Based on the evaluation of the six elements, the internal audit capability of BPKP Representative of East Kalimantan Province is at level 3 (integrated) with the record.